Effect of Moringa Leaves Flour (Moringa oleifera) Addition In Making Cake Onde-Onde Using Mocaf Flour - Purba, Ria Agatha (University of Brawijaya, 2019)
The purpose of this research was to find the nutritional content of cake onde-onde made from mocaf flour with the addition of moringa leaves flour and to find the best formulation of making cake onde-onde. This research was performed using completely random design with two factors, first factor was the ratio of wheat flour and mocaf flour (T): T1=100%:0%, T2= 5%:25%, T3= 50%:50%, and T4= 25%:75%. The second was moringa leaves flour percentage (K): K1=0%, K2=2%, and K3=4%. Parameters analyzed were moisture content (%), ash content (%), fat content (%), protein content (%), carbohydrate content (by difference), dietary fiber content (%), colour index (oHue), and texture (g/mm2). The results showed that the ratio of wheat flour and mocaf flour had highly significant effect on moisture content, ash content, fat content, protein content, carbohydrate content, dietary fiber content, and texture (g/mm2). The addition of Moringa leaves flour had highly significant effect on ash content, protein content, carbohydrate content, dietary fiber content, and colour index (oHue). Based on protein content, the best cake onde-onde was made with 75% of wheat flour and 25% mocaf flour and the addition of 2% moringa leaves flour.